89 Nutrition and Feeding of the Modern Hyperprolific Sow - Greiner, Laura L (J Anim Sci, 2020)
Over the last 25 years, the sow has developed to have a leaner body mass to address the need for leaner, fast growing offspring. The leaner body mass results in a female that biologically can have a lower feed intake. Furthermore, the number of pigs born per litter and milk production have also increased during the same timeframe. Much research has been conducted over the years to investigate the amino acid and energy requirements of both the lactating and gestating sow; however, application of the research has resulted in varied responses. The varied responses can be related to sow health, environmental influences, litter growth rates, and anticipated body reserve changes during lactation. Furthermore, calculations associated with the regression of reproductive tissue after farrowing can complicate the analysis of amino acid requirements. This presentation will discuss some of the recent research associated with feeding the modern sow, potentially challenging some of the differences in data, and offering some thoughts on looking towards the next 25 years of sow production.